WAJAH PENYIARAN TELEVISI DIGITAL INDONESIA: TINJAUAN REVISI UNDANG-UNDANG NOMOR 32 TAHUN 2002 TENTANG PENYIARAN - Sindu, Jaka (Jurnal Insani, 2018)
United Nations through the International Telecommunication Union set the date of June 17, 2015 as the deadline for countries around the world to migrate from Analog Television Broadcasting to Digital Television Broadcasting--Analog Switch Off (ASO) (The Geneva 2006 Frequency Plan-GE 06 Agreement). 99 percent of the world's territories have implemented it. But Indonesia until 2017 has not been able to carry out these obligations because it is still constrained regulations that do not yet exist. Law Number 32 Year 2002 on Broadcasting does not explicitly regulate the issue. The Government through the Ministry of Communications and Information then issued two ministerial regulations namely: Ministerial Regulation Number 22/2011, on the Implementation of Terrestrial Digital Television Broadcasting of Free To Air, and Ministerial Regulation Number 23/2011 on Master Plan of Radio Frequency for Television Terrestrial Digital Broadcasting On Radio Ribbons 478 - 694 MHz. Both regulations were defeated in the judicial review in the Constitutional Court by the Institute of Community and Media Development (Incode) and also again lost in the State Administrative Court - PTUN by the Association of Indonesian Television Network-ATJI.Then the government changed the public-owned frequency paradigm into state property, the radio frequency spectrum (used as a television broadcasting channel) is a limited natural resource and national assets controlled by the state and administered by the government for maximum use for the people's prosperity in accordance with Article 33 paragraph (3) of the 1945 Constitution, and appoint LPP TVRI as the sole operator of digital frequency organizer. The Ministry of Communications and Information submitted a revision of Law Number 32 Year 2002 on Broadcasting to accommodate the regulation, but although it was decided by a vote in the Legislation Body of the House of Representatives, some losing party factions still could not accept the decision because it was considered a monopoly act against Indonesian television broadcasting, and hampered the democratization of broadcasting.